2020
DOI: 10.52386/neurona.v36i4.89
|View full text |Cite
|
Sign up to set email alerts
|

Nilai Diagnostik Skor Stroke Dave Unhas Pada Penderita Stroke Iskemik Kardioemboli Dengan Fibrilasi Atrium

Abstract: DIAGNOSTIC VALUE OF DAVE UNHAS STROKE SCORE IN CARDIOEMBOLIC ISCHEMIC STROKE PATIENTS WITH ATRIAL FIBRILLATIONABSTRACTIntroduction: It is important to diagnose cardioembolic ischemic stroke quickly especially in the absence of CT scan/MRI, besides having a poor prognosis, cardioembolic ischemic stroke also has high disability and death rates.Aim: To investigate the diagnostic value of Dave Unhas Stroke Score (DUSS) in cardioembolic ischemic stroke patients with atrial fibrillation (AF).Methods: This was a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…However, at an older age (>60 years), the cardioembolic stroke cases in females were slightly higher (18.52%) than those in male's patients (17.9%). This result is comparable with a study in Makassar 14 that showed at an older age (>60 years), female experience more cardioembolic stroke than male patient. This is because elderly women are more likely to have hypertension, myocardial dysfunction & ischemia, ventricular hypertrophy, atrial fibrillation and heart failure due to the loss of the safeguarding effect of estrogen to prevent cardiovascular disease.…”
Section: Sex and Agesupporting
confidence: 89%
See 1 more Smart Citation
“…However, at an older age (>60 years), the cardioembolic stroke cases in females were slightly higher (18.52%) than those in male's patients (17.9%). This result is comparable with a study in Makassar 14 that showed at an older age (>60 years), female experience more cardioembolic stroke than male patient. This is because elderly women are more likely to have hypertension, myocardial dysfunction & ischemia, ventricular hypertrophy, atrial fibrillation and heart failure due to the loss of the safeguarding effect of estrogen to prevent cardiovascular disease.…”
Section: Sex and Agesupporting
confidence: 89%
“…15,16 In this study, most cardioembolic stroke patients were in the 45-65 year old age group (55.55%) followed by >65 years old age group (28.40%) which was consistent with the previous study in Makassar. 14 With aging, the incidence of cardioembolic stroke was increasing because atrial fibrillation, the most frequent cause of cardioembolic stroke, is more common in the elderly age group.…”
Section: Sex and Agementioning
confidence: 99%